Association between sickle cell anemia and alpha thalassemia reveals a high prevalence of the α3.7 triplication in congolese patients than in worldwide series. Issue 1 (9th March 2017) - Mikobi, Tite Minga; Lukusa, Prosper Tshilobo; Aloni, Michel Ntetani; Lumaka, Aimé; Akilimali, Pierre Zalagile; Devriendt, Koenraad; Matthijs, Gert; Mbuyi Muamba, Jean‐Marie; Race, Valerie
Abstract : Background: Information about the association with alpha thalassemia in sickle cell patients is unknown in the Democratic Republic of Congo. There is very little data on the alpha thalassemia in patients suffering from sickle cell anemia in Central Africa, and their consequences on the clinical expression of the disease. Methods: A cross‐sectional study was conducted in 106 sickle cell patients living in the country's capital Kinshasa. The diagnosis of sickle cell anemia was confirmed with a molecular test using PCR‐RFLP (restriction fragment length polymorphism) technique. The diagnosis of thalassemia was performed by the technique of multiplex ligation dependent probe amplification. Results: The mean age of our patients was 22.4±13.6 years. The α 3.7 heterozygous deletion, the α 3.7 homozygous deletion and the α 3.7 triplication were respectively encountered in 23.6%, 25.5%, and 11.3% of patients. Patients with normal αα/αα genotype represented 39.6% of the study population. The average of severe vaso‐occlusive crises, the rates of blood transfusions per year, the rate of osteonecrosis, cholelithiasis and leg ulcers were significantly lower in the group of patients with α 3.7 homozygous deletion and α 3.7 triplication. Conclusion: The prevalence of α 3.7 triplication was higher in sickle cell patients in the Democratic Republic of Congo than in worldwide series. The α 3.7 triplication and α 3.7 homozygous deletion were associated with less severe forms of the Sickle cell anemia in Congolese patients. These results showed the need to investigate systematically the alpha‐globin gene mutations in sickle cell population in Central Africa.